Preparation process of nanometer hafnium silicide

CN123002855APending Publication Date: 2026-10-30HUNAN HUAWEI JINGCHENG MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611502311.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

针对硅化铪一维纳米结构的高效可控制备方法尚未见公开报道

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123002855A_ABST
    Figure CN123002855A_ABST
Patent Text Reader

Abstract

The application relates to the field of inorganic nanometer materials, in particular to a preparation process of nanometer hafnium silicide, which comprises the following steps: uniformly mixing hafnium powder, silicon powder, sodium nitrate, carboxymethyl cellulose and a catalyst to obtain mixed materials, wherein the catalyst is composed of nanometer nickel powder and rare earth chloride; ball-milling the mixed materials under the protection of argon and then pressing the mixed materials into a blank; loading the blank into a graphite crucible of a vacuum self-propagating furnace, taking magnesium powder and sodium nitrate as an igniter, vacuumizing, then introducing argon, heating and igniting the igniter, and then carrying out a self-propagating reaction; after sufficient reaction, heat preservation is carried out in a heat preservation temperature interval, and the furnace is cooled to room temperature, so that the nanometer hafnium silicide is obtained; the process is simple, the reaction time is short, the energy consumption is low, the equipment requirement is simple, the raw materials are easy to obtain, one-dimensional nanometer hafnium silicide can be obtained without complex post-treatment, and the large-scale production can be easily realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of inorganic nanomaterials, specifically to a preparation process for nano-hafnium silicide. Background Technology

[0002] Hafnium silicide is an important refractory metal silicide with high melting point, high hardness, good high-temperature oxidation resistance, excellent high-temperature conductivity, and chemical stability. It has broad application prospects in microelectronic devices, high-temperature structural materials, electrothermal elements, field emission cathodes, and thermal protection coatings for aerospace applications. In particular, when the microstructure of hafnium silicide changes from conventional bulk or micron-sized particles to nanoscale one-dimensional structures, such as nanowires, nanorods, and nanoribbons, its specific surface area increases significantly, potentially leading to new physicochemical properties, such as excellent field emission performance, enhanced catalytic activity, good flexibility, and quantum confinement effects. Therefore, the preparation of one-dimensional hafnium silicide nanomaterials has significant scientific and engineering application value.

[0003] Self-propagating high-temperature synthesis is a material synthesis method that utilizes the exothermic reaction itself to sustain the process. This method offers advantages such as rapid reaction speed, low energy consumption, simple equipment, high product purity, and ease of large-scale production. In existing technologies for the self-propagating high-temperature synthesis of hafnium silicide, hafnium powder and silicon powder are typically mixed and pressed into a preform, then ignited to obtain blocky or powdered hafnium silicide products. Due to the high temperature and rapid reaction rate of the self-propagating reaction, the product morphology is usually irregular particles or dense masses, making it difficult to directly form one-dimensional structures such as nanowires and nanorods. No efficient and controllable preparation method for one-dimensional hafnium silicide nanostructures has been publicly reported.

[0004] Therefore, developing a simple, low-cost, and morphology-controllable method for preparing one-dimensional hafnium nanostructures is of great practical significance and application potential. Summary of the Invention

[0005] Purpose of the invention: To address the above-mentioned technical problems, this invention proposes a preparation process for nano-hafnium silicide.

[0006] The technical solution adopted is as follows: A process for preparing nano-hafnium silicide includes: Hafnium powder, silicon powder, sodium nitrate, carboxymethyl cellulose and catalyst are mixed evenly to obtain a mixture, wherein the catalyst is composed of nano-nickel powder and rare earth chloride; The mixture was ball-milled under argon protection and then pressed into a blank. The billet is placed in a graphite crucible in a vacuum self-propagating furnace. Magnesium powder and sodium nitrate are used as igniters. After evacuation, argon gas is introduced and heated to ignite the igniters, causing a self-propagating reaction. After the reaction is complete, the billet is kept at a constant temperature within the specified range and then cooled to room temperature with the furnace to obtain the final product.

[0007] Furthermore, the molar ratio of hafnium powder to silicon powder is 1:2. At this molar ratio, hafnium and silicon can form hafnium silicide with HfSi2 as the main phase according to stoichiometry.

[0008] Furthermore, the amount of nano-nickel powder added is 0.8%-1.2% of the total mass of hafnium powder and silicon powder, and the amount of rare earth chloride added is 0.2%-0.4% of the total mass of hafnium powder and silicon powder. As a catalytically active component, nano-nickel powder can form low-melting-point droplets with silicon at high temperatures, promoting gas-liquid-solid growth. Rare earth chloride, as an auxiliary catalyst and chlorine source, can provide chlorine species during the reaction, forming volatile hafnium and silicon chloride intermediates, enhancing gas-phase transport capability. Simultaneously, rare earth elements can modify the surface properties of nickel-silicon droplets, which is beneficial for the directional growth of one-dimensional structures. If the amount of nano-nickel powder is too low, the number of catalytic droplets will be insufficient, and the nanowire yield will decrease; if the amount is too high, coarse particles or lumps will easily form. If the amount of rare earth chloride is too low, the chlorine source will be insufficient, and the gas-phase transport capability will be weak; if the amount is too high, it will lead to excessive release of chlorine-containing species, causing raw material loss and environmental pollution.

[0009] Furthermore, the ball milling speed is 500-1000 rpm, and the ball milling time is 5-15 h. Under these ball milling conditions, the components can be fully and uniformly mixed, the catalyst is well dispersed in the hafnium powder and silicon powder matrix, and the active structure of the catalyst will not be destroyed or the powder will be severely agglomerated due to excessive ball milling intensity.

[0010] Furthermore, the pressing pressure is 12-15 MPa. Within this pressure range, the preform can obtain sufficient molding strength while maintaining appropriate porosity, which is beneficial for heat transfer and diffusion of gaseous substances during the self-propagating reaction, promoting the growth of one-dimensional nanostructures.

[0011] Furthermore, the amount of sodium nitrate added to the mixture is 3%-5% of the total mass of hafnium powder and silicon powder. Sodium nitrate acts as an auxiliary oxidant and exothermic agent in the self-propagating reaction, regulating the reaction temperature to ensure its stability and to guarantee that the reaction temperature reaches the required range. If the amount of sodium nitrate is too low, the reaction temperature will be insufficient, resulting in incomplete reaction; if the amount is too high, the reaction will be too vigorous, easily leading to cracking of the green body or sintering of the product.

[0012] Furthermore, the amount of carboxymethyl cellulose added is 0.4%-0.8% of the total mass of hafnium powder and silicon powder. As a binder, carboxymethyl cellulose improves the formability of the mixed powder, giving the green body sufficient strength after pressing, facilitating furnace loading and stacking. Simultaneously, carboxymethyl cellulose decomposes at high temperatures, leaving no harmful impurities in the final product.

[0013] Furthermore, the rare earth chloride is cerium chloride and / or lanthanum chloride. Cerium chloride and lanthanum chloride can decompose or react with hafnium and silicon at high temperatures to generate chloride species, providing a chlorine source. At the same time, cerium and lanthanum can serve as surface-active components to modify catalytic droplets and promote one-dimensional growth.

[0014] Furthermore, the holding temperature range is 1000-1200℃. After the self-propagating reaction is completed, holding the reaction system within this range is beneficial for the further growth and crystallization of nanowires, reduces structural defects, and improves the crystallinity and purity of the product.

[0015] Furthermore, the nano-hafnium silicide prepared by the process of the present invention has a one-dimensional structure.

[0016] The basic technical concept of this invention is as follows: using hafnium powder and silicon powder as reaction raw materials, adding sodium nitrate as a heating aid, adding carboxymethyl cellulose as a molding binder, and adding a composite catalyst composed of nano-nickel powder and rare earth chlorides, the components are fully mixed and homogeneous by ball milling, and then the mixture is pressed into a green body. In a vacuum self-propagating furnace, magnesium powder and sodium nitrate are used as igniters. The igniters are ignited, and the magnesium powder combustion ignites the green body to undergo a self-propagating high-temperature synthesis reaction. After the reaction is completed, the green body is kept at a holding temperature range of 1000-1200℃ and cooled with the furnace to obtain nano-hafnium silicide with a one-dimensional structure.

[0017] The core mechanism of this invention lies in the following: During the self-propagating high-temperature synthesis process, nano-nickel powder and silicon powder form low-melting-point nickel-silicon alloy droplets at high temperatures. These droplets serve as the catalytic center for the gas-liquid-solid growth mechanism. Rare earth chlorides decompose at high temperatures or react with hafnium and silicon, providing chloride species to form hafnium chloride and silicon chloride gaseous intermediates. These gaseous intermediates are captured by the nickel-silicon alloy droplets, react on the droplet surface, and deposit to generate hafnium silicide. Due to the directional adsorption and interfacial reaction of the droplets on the gaseous species, after reaching supersaturation, they precipitate at the liquid-solid interface and preferentially grow along the energy-favorable direction to form a one-dimensional nanostructure. Rare earth elements can modify the surface energy of the nickel-silicon droplets, improving the stability and catalytic selectivity of the droplets, which is beneficial for obtaining nanowires with uniform diameter and long length.

[0018] During the self-propagating reaction, the reaction front temperature is relatively high, typically exceeding 1600℃. After the reaction is complete, holding the reaction system at 1000-1200℃ promotes further reaction of unreacted components, while also encouraging continued growth of nanowires and lattice refinement, eliminating some structural defects, and increasing the crystallinity of the product. If the holding temperature is too low, the nanowires will not grow sufficiently and will be short; if the holding temperature is too high, the nanowires may sinter or coarsen, increasing in diameter, or even transforming into particles.

[0019] The present invention has a simple process, short reaction time, low energy consumption, simple equipment requirements, readily available raw materials, and can obtain one-dimensional nano hafnium silicide without complicated post-processing, making it easy to achieve large-scale production. Attached Figure Description

[0020] Figure 1 The image shows the XRD pattern of the nano-hafnium silicide prepared in Example 1.

[0021] Figure 2 This is a SEM image of the nano-hafnium silicide prepared in Example 1. Detailed Implementation

[0022] Unless otherwise specified in the examples, the conditions were performed under standard conditions or as recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products. Techniques not mentioned in this invention refer to existing technologies. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0023] Example 1:

[0024] A process for preparing nano-hafnium silicide: Weigh out hafnium powder, silicon powder, sodium nitrate, carboxymethyl cellulose, nano-nickel powder, and cerium chloride. The hafnium powder has a purity of not less than 99.6% and an average particle size of 200 mesh; the silicon powder has a purity of not less than 99% and an average particle size of 300 mesh; the nano-nickel powder has an average particle size of 80 nm and a purity of not less than 99.9%; and the cerium chloride has a purity of not less than 99%. The total mass of hafnium powder is 168.8 g, silicon powder is 53.1 g, and the total mass of hafnium powder and silicon powder is 221.9 g. The amount of nano-nickel powder added is 1% of the total mass of hafnium powder and silicon powder, the amount of cerium chloride added is 0.3% of the total mass of hafnium powder and silicon powder, the amount of sodium nitrate added is 4% of the total mass of hafnium powder and silicon powder, and the amount of carboxymethyl cellulose added is 0.6% of the total mass of hafnium powder and silicon powder.

[0025] Under argon protection, the above raw materials were placed in a vacuum ball mill jar, and zirconia grinding balls were added at a ball-to-material ratio of 10:1. The ball mill jar was evacuated, then filled with high-purity argon for protection and sealed. The mixture was ball-milled for 10 hours at 800 rpm in a planetary ball mill. After milling, the mixture was removed from an argon-filled glove box, sieved to remove the grinding balls, and a uniform mixed powder was obtained.

[0026] The ball-milled mixed powder was pressed into a disc-shaped blank using a hydraulic press at 13 MPa. The blank was placed in a graphite crucible in a vacuum self-propagating furnace, with 0.5 g of magnesium powder and 0.25 g of sodium nitrate placed on top as igniters. After closing the furnace door, a vacuum was created, and high-purity argon gas was introduced, repeatedly replacing the air in the furnace three times to reduce the oxygen content. Then, maintaining a slight positive pressure of argon gas, the tungsten filament was heated to 800°C, igniting the igniters. The magnesium powder burned, releasing heat and igniting the blank in a self-propagating reaction. The highest reaction temperature, monitored by an infrared thermometer, reached 1635°C. After the reaction was completed, the furnace temperature control mode was switched to programmable temperature control, setting the target temperature to 1100°C. When the thermocouple detected that the furnace temperature had naturally dropped to 1100°C, the temperature control system automatically started heating for compensation, stabilizing the furnace temperature at 1100°C and holding it for 2 hours. Finally, the furnace was cooled to room temperature. After the furnace was opened, the product was washed three times with 0.5 mol / L dilute hydrochloric acid, then washed with deionized water until neutral, and vacuum dried to obtain nano-hafnium silicide with a one-dimensional structure. See the XRD pattern below. Figure 1 See SEM image. Figure 2 The phase purity is 96.7%.

[0027] Example 2:

[0028] The process is basically the same as in Example 1, except that the amount of nano-nickel powder added is 1.2% of the total mass of hafnium powder and silicon powder, the amount of cerium chloride added is 0.4% of the total mass of hafnium powder and silicon powder, the amount of sodium nitrate added is 5% of the total mass of hafnium powder and silicon powder, and the amount of carboxymethyl cellulose added is 0.8% of the total mass of hafnium powder and silicon powder. The product is nano-hafnium silicide with a one-dimensional structure and a phase purity of 97.3%.

[0029] Example 3:

[0030] The process is basically the same as in Example 1, except that the amount of nano-nickel powder added is 0.8% of the total mass of hafnium powder and silicon powder, the amount of cerium chloride added is 0.2% of the total mass of hafnium powder and silicon powder, the amount of sodium nitrate added is 3% of the total mass of hafnium powder and silicon powder, and the amount of carboxymethyl cellulose added is 0.4% of the total mass of hafnium powder and silicon powder. The product is nano-hafnium silicide with a one-dimensional structure and a phase purity of 96.2%.

[0031] Example 4:

[0032] The process is basically the same as in Example 1, except that the amount of nano-nickel powder added is 1.2% of the total mass of hafnium powder and silicon powder, the amount of cerium chloride added is 0.2% of the total mass of hafnium powder and silicon powder, the amount of sodium nitrate added is 5% of the total mass of hafnium powder and silicon powder, and the amount of carboxymethyl cellulose added is 0.4% of the total mass of hafnium powder and silicon powder. The product is nano-hafnium silicide with a one-dimensional structure and a phase purity of 96.6%.

[0033] Example 5:

[0034] The process is basically the same as in Example 1, except that the amount of nano-nickel powder added is 0.8% of the total mass of hafnium powder and silicon powder, the amount of cerium chloride added is 0.4% of the total mass of hafnium powder and silicon powder, the amount of sodium nitrate added is 3% of the total mass of hafnium powder and silicon powder, and the amount of carboxymethyl cellulose added is 0.8% of the total mass of hafnium powder and silicon powder. The product is nano-hafnium silicide with a one-dimensional structure and a phase purity of 96.0%.

[0035] Example 6:

[0036] The results are basically the same as in Example 1, except that the heat preservation temperature range is 1000℃, the product is nano-hafnium silicide with a one-dimensional structure, and the phase purity is 96.4%.

[0037] Example 7:

[0038] The results are basically the same as in Example 1, except that the heat preservation temperature range is 1200℃, the product is nano-hafnium silicide with a one-dimensional structure, and the phase purity is 96.9%.

[0039] Comparative Example 1: The product is basically the same as in Example 1, except that no nano-nickel powder and cerium chloride are added. The product morphology is irregular particles and blocks, no nanowires are observed, and the purity of hafnium silicide phase in the product is 96.5%.

[0040] Comparative Example 2: The results were basically the same as in Example 1, except that no nano-nickel powder was added, the product morphology was flake-like and granular, no nanowires were observed, and the purity of hafnium silicide phase in the product was 96.3%.

[0041] Comparative Example 3: The product is basically the same as Example 1, except that cerium chloride is not added. The product contains only a small amount of nanowires and is mostly particles. The purity of hafnium silicide phase in the product is 94.8%.

[0042] Comparative Example 4: The product is basically the same as in Example 1, except that it is not heated at 1100°C for 2 hours. The product contains only a small amount of nanowires, and most of them are short rods and particles. The purity of hafnium silicide phase in the product is 96.2%.

[0043] The preparation method for this comparative example is as follows: The ball-milled mixed powder was pressed into a disc-shaped blank using a hydraulic press at 13 MPa. The blank was placed in a graphite crucible in a vacuum self-propagating furnace, and 0.5 g of magnesium powder and 0.25 g of sodium nitrate were placed on top of the blank as ignition agents. After closing the furnace door, a vacuum was drawn, and high-purity argon gas was introduced, repeatedly replacing the air in the furnace three times to reduce the oxygen content. Then, maintaining a slight positive pressure of argon gas, the tungsten filament was heated to 800°C, igniting the ignition agents. The magnesium powder burned exothermically, igniting the blank in a self-propagating reaction. The highest reaction temperature, monitored by an infrared thermometer, reached 1635°C. After the reaction was completed, the product was cooled to room temperature with the furnace. After opening the furnace, the product was washed three times with 0.5 mol / L dilute hydrochloric acid, then washed with deionized water until neutral, and vacuum dried to obtain the final product.

[0044] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A process for preparing nano-hafnium silicide, characterized in that, include: Hafnium powder, silicon powder, sodium nitrate, carboxymethyl cellulose and catalyst are mixed evenly to obtain a mixture, wherein the catalyst is composed of nano-nickel powder and rare earth chloride; The mixture was ball-milled under argon protection and then pressed into a blank. The billet is placed in a graphite crucible in a vacuum self-propagating furnace. Magnesium powder and sodium nitrate are used as igniters. After evacuation, argon gas is introduced and heated to ignite the igniters, causing a self-propagating reaction. After the reaction is complete, the billet is kept at a constant temperature within the specified range and then cooled to room temperature with the furnace to obtain the final product.

2. The preparation process of nano-hafnium silicide as described in claim 1, characterized in that, The molar ratio of hafnium powder to silicon powder is 1:

2.

3. The preparation process of nano-hafnium silicide as described in claim 1, characterized in that, The amount of nano-nickel powder added is 0.8%-1.2% of the total mass of hafnium powder and silicon powder, and the amount of rare earth chloride added is 0.2%-0.4% of the total mass of hafnium powder and silicon powder.

4. The preparation process of nano-hafnium silicide as described in claim 1, characterized in that, The ball milling speed is 500-1000 rpm, and the ball milling time is 5-15 hours.

5. The preparation process of nano-hafnium silicide as described in claim 1, characterized in that, The pressure during pressing is 12-15 MPa.

6. The preparation process of nano-hafnium silicide as described in claim 1, characterized in that, The amount of sodium nitrate added to the mixture is 3%-5% of the total mass of hafnium powder and silicon powder.

7. The preparation process of nano-hafnium silicide as described in claim 1, characterized in that, The amount of carboxymethyl cellulose added is 0.4%-0.8% of the total mass of hafnium powder and silicon powder.

8. The preparation process of nano-hafnium silicide as described in claim 1, characterized in that, The rare earth chloride is cerium chloride and / or lanthanum chloride.

9. The preparation process of nano-hafnium silicide as described in claim 1, characterized in that, The insulation temperature range is 1000-1200℃.

10. The preparation process of nano-hafnium silicide as described in claim 1, characterized in that, The nano-hafnium silicide has a one-dimensional structure.